PENGARUH DIVERSIFIKASI PORTOFOLIO KREDIT TERHADAP TINGKAT RISIKO KREDIT DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI Studi pada Bank Umum di Indonesia - , RYANA WIDYATINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A formal control system supports the success of loan portfolio diversification strategy. Good corporate governance as a formal control system can be support the success of implementation of loan portfolio diversification strategy with the result risk profile will occur in the low level. The aim of this study is to explore the effect of loan portfolio diversification towards credit risk level with good corporate governance as a moderating variable. Study on General Bank in Indonesia. The panel data analysis used eviews version 7.2. Sample of the data were general banks that had registered at BEI in 2009 to 2012 period. The collecting of the data was based on the certain criterions and there were 20 banks. The results of this research showed that good corporate governance moderate loan portfolio diversification strategy, so it can decrease credit risk level in the low level. The positive effect of good corporate governance in moderating the effect of loan portfolio diversification toward credit risk level was consistent not only based on by type of loan but also economic sector.